Quality of life in patients with psoriasis - Morrison, Mercedes Shamilla (My University, 2020)
Background Psoriasis(PsO) is a chronic skin disease that is often associated with impaired health-related quality of life (HRQoL). To date there are limited data on HRQoL in South Africans with PsO. Objective The aim of the present study was to assess HRQoL in patients with PsO in urban Gauteng, South Africa. Patients and Methods-A cross-sectional study was conducted in patients with PsO attending Dermatology clinics at three hospitals of the Wits Academic Complex, Johannesburg. Data collection included demographics, Psoriasis area and severity index (PASI) and two dermatology HRQoL questionnaires, namely the Dermatology life quality index (DLQI) and PsO-specific, Psoriasis disability index (PDI). Results-Of the 105 patients who participated in the study, there was almost an equal number of men and women, with a mean (SD) age and disease duration of 53,04 (14.65) years and 15 (20) years, respectively. Most patients had plaque type PsO (98.1%) and 30,5% had psoriatic arthritis. The median (IQR) PASI, DLQI and PDI scores were 5,5(10,4), 8(10) and 10(15), respectively. Predictors of worse DLQI and PDI scores were PASI>10 (p=0.011 and p=0.002), respectively, and younger age (p=0.002 and p=0.000), respectively. In addition, DLQI was also negatively affected by marital status, genital involvement of psoriasis and smoking status. Conclusion Patients with PsO from Johannesburg, South Africa seem to have impaired HRQoL as assessed by both DLQI and PDI and more so with moderate to severe skin involvement and in younger patients, findings that are similar to those reported in other populations.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Medicine in Dermatology to the Faculty of Health Sciences, School of Medicine, University of the Witwatersrand, Johannesburg, 2017